2022
DOI: 10.20524/aog.2022.0722
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile infection in cancer patients receiving immune checkpoint inhibitors

Abstract: Background Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment, but are associated with immune-mediated diarrhea and colitis (IMDC). Clostridioides difficile infection (CDI) can cause infectious diarrhea with overlapping symptoms. Thus, we sought to elucidate the characteristics of CDI in patients treated with ICI, in the context of IMDC. Methods We conducted a retrospective, single-center study of adult cancer patients (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…A retrospective single-center study explored the attributes of CDI in patients undergoing therapy with ICI in the presence of IMDC. The study concluded that the concurrence of CDI and IMDC is associated with prolonged symptom duration (20 vs. 5 days, p=0.003) and a reported higher rate of grade 3-4 diarrhea (41% vs. 7%, p=0.033) [ 13 ]. Similarly, in our case, the patient was started on treatment for the suggested IMDC with high-dose steroids.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective single-center study explored the attributes of CDI in patients undergoing therapy with ICI in the presence of IMDC. The study concluded that the concurrence of CDI and IMDC is associated with prolonged symptom duration (20 vs. 5 days, p=0.003) and a reported higher rate of grade 3-4 diarrhea (41% vs. 7%, p=0.033) [ 13 ]. Similarly, in our case, the patient was started on treatment for the suggested IMDC with high-dose steroids.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has been proposed and evaluated in several investigations. Previous evidence suggests that ICI-related colitis increases susceptibility to gastrointestinal tract infections such as Clostridioides difficile 37 , non- C. diff. bacterial, and viral infections 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, 27 among 345 patients who received 492 terms of chemotherapy regimens, 36 (7.3%) had grade 2 or higher diarrhea, and eight had CDI without prior exposure to antibiotics. In a prospective study, 27 five cases of CDI were diagnosed among 263 patients with lung In a recent retrospective study, 28 among 421 patients with cancer receiving immunotherapy including programmed death-1 or its ligand inhibitors or cytotoxic T-lymphocyte-associated antigen 4 inhibitors, 41 patients had CDI (9.7%). Prior use of antibiotics and PPIs were significantly more common among individuals who CDI after immune checkpoint inhibitors exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study, 28 among 421 patients with cancer receiving immunotherapy including programmed death-1 or its ligand inhibitors or cytotoxic T-lymphocyte-associated antigen 4 inhibitors, 41 patients had CDI (9.7%). Prior use of antibiotics and PPIs were significantly more common among individuals who developed CDI after immune checkpoint inhibitors exposure.…”
Section: Discussionmentioning
confidence: 99%